Sistem Informasi Milktrack Berbasis Website untuk Recording Penyetoran Susu (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Milk delivery recording at the Karangploso Agricultural Cooperative (KUD) is still performed manually using paper, which has the potential to cause recording errors, delays in data compilation, and a lack of efficiency in information management. This study aims to develop a web-based MilkTrack information system and to measure the feasibility, usability, and user acceptance of the developed system. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques included interviews, questionnaires, and literature reviews, involving 39 respondents comprising farmers, collection point administrators, KUD administrators, and KUD managers. Research instruments consisted of a needs analysis questionnaire, the System Usability Scale (SUS), and the Technology Acceptance Model (TAM). The research results indicate that the SUS score of 73.14 falls into the “acceptable” category, with a score range of 62.50–87.50. The TAM results show an average score ranging from 3.69 to 4.36, falling into the “agree” to “strongly agree” categories. The reliability test yielded a Cronbach’s Alpha value of 0.952, which falls into the “very high” category. Based on these results, the MilkTrack system is deemed suitable for use and capable of improving efficiency, accuracy, and ease in recording milk delivery at KUD Karangploso.